Retail selling - Bodle, Yvonne Gallegos; Corey, Joseph A. (New York : Gregg Division, McGraw-Hill, 1977)
Discusses the qualifications for and the challenges, opportunities, and rewards of a job in sales.
Περιέχει βιβλιογραφία.
Keywords: Selling; Retail trade; Selling -- Vocational guidance; Vocational guidance